EVALUATION OF WORK POSTURE USING THE CTD RISK INDEX METHOD TO REDUCE THE RISK OF MUSCLE INJURY IN THE BATIK CAP INDUSTRY - Pratiwi, Indah; Pertiwi, Astrid Winahyu (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2023)
Making stamped batik goes through 5 stages, namely tasting, dyeing color, removing hot and cold tubs, and drying. This process takes place repeatedly for a long time, causing workers to potentially experience musculoskeletal complaints and the risk of Cumulative Trauma Disorders (CTDs). The purpose of this study was to determine whether batik Nilo Tirto workers were at risk for developing CTDs or not. This research was conducted by using a method to determine the level of worker complaints with a Nordic Body Map (NBM) questionnaire. After knowing each class of worker complaints, the CTDs Risk Index method is used to determine the risk score for muscle injury in workers. If the score is > 1, it is relatively unsafe, so it needs improvement. The 2 most significant scores on the CTDs Risk Index worksheet will be analyzed further to determine the risk factors for musculoskeletal use using the PLIBEL Checklist. The results obtained are, there are 2 workstations that have the highest score on the CTDs Risk Index, namely color dyeing and cold bathing. This is caused by awkward body postures when working, repetitive movements, and poor workstation conditions, so the repair needs to be done. The results of this study can be used for improvements to the workstation for dyeing color and cold tubing in the form of design proposals and the work postures of the two workers.